Potter and the Balance of the Ecosystem as the Foundation of the Bioethical Morality (Revista Iberoamericana de Bioética, 2021)
Ethical thought ascribed great weight to the central nature of the human being until the 20th century. Historically, ecosystem life has always been considered a field divorced from morality, and the mechanistic explanations of life justified these choices. This worldview proved to be extremely harmful, as it promoted an imbalance in the ecosystem and allowed human beings to act on nature without moral parameters. This in turn threatened the future survival of human beings themselves. Van Rensselaer Potter’s bioethics identified the need to rescue and extend the environmental dimension to include all biosphere life under ethical protection. Faced with this scenario, the question to be asked is: by basing the morality of bioethics on a balanced ecosystem to ensure humanity’s survival in the future, was Potter able to overcome the traditional anthropocentric view of ethics? This is a literature review with an analytical-interpretive nature. First, we sought to analyse how Potter, inspired by Aldo Leopold, rescued and expanded the ethical dimension to include nature. Next, we sought to base Potter’s choice on the balanced ecosystem as the foundation of morality, and not on the recognition of the intrinsic value of each individual life. We conclude that in an attempt to move away from ethical anthropocentrism, Potter’s bioethics sought to recover an ancestral wisdom, based on the idea of a balanced ecosystem and in this balance, Potter found the biological wisdom to support the morality of bioethics, even though he committed a naturalistic fallacy.
Keywords: Potter; morality; ecosystem; bioethics